2018
DOI: 10.1590/1414-431x20187702
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy: biochemical alterations involved in reduction of damage induced by exhaustive exercise

Abstract: When exercises are done in intense or exhaustive modes, several acute biochemical mechanisms are triggered. The use of cryotherapy as cold-water immersion is largely used to accelerate the process of muscular recovery based on its anti-inflammatory and analgesic properties. The present study aimed to study the biochemical effects of cold-water immersion treatment in mice submitted to exercise-induced exhaustion. Swiss albino mice were divided into 4 treatment groups: control, cold-water immersion (CWI), swimmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
3
0
2
Order By: Relevance
“…The time chosen was sufficient to cool the area according to the literary findings. These corroborate the study by Furtado et al 10 , who applied in their study the protocol of immersion in cold water for five consecutive days, after a single session of exhaustive exercise, with the temperature of 12°C, for 12 minutes, immersing the whole body. They also demonstrated that treatment with immersion in cold water after a session of intense exercise was able to decrease the formation and damage of ROS and increase cell viability, favoring a faster recovery of muscle tissue.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The time chosen was sufficient to cool the area according to the literary findings. These corroborate the study by Furtado et al 10 , who applied in their study the protocol of immersion in cold water for five consecutive days, after a single session of exhaustive exercise, with the temperature of 12°C, for 12 minutes, immersing the whole body. They also demonstrated that treatment with immersion in cold water after a session of intense exercise was able to decrease the formation and damage of ROS and increase cell viability, favoring a faster recovery of muscle tissue.…”
Section: Discussionsupporting
confidence: 90%
“…The therapeutic protocol adopted for five consecutive days aimed to analyze the initial effects of the application of different electrotherapeutic resources: immersion cryotherapy, LLLT and ILIB, in the tissue healing process in healthy organisms and patients with kidney disease associated with DM. In the literature, there is still little described about the effects of the application of these resources, in view of the conditions of these associated metabolic disorders 10 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all types of exercises are good for health. For instance, an exhaustive exercise may damage multiple organs, which is induced by oxidative stress, inflammation, mitochondrial dysfunction, and hormonal changes (Olaìh et al, 2015;Kawanishi et al, 2016;Ke et al, 2016;Liu et al, 2017;Furtado et al, 2018;Yada et al, 2018;Zhang et al, 2019). Certainly, if it is one bout of acute exhaustive exercise, the body can adapt to the imbalances and then recover to the normal state in a few days.…”
Section: Introductionmentioning
confidence: 99%
“…Занурення в холодну воду широко використовується для прискорення процесу відновлення м'язів завдяки протизапальним та знеболюючим ефектам [3,9]. При цьому знижується вироблення реактивних речовин, відновлюється окисно-відновлювальний баланс, підвищується життєздатність клітин [9].…”
Section: вступunclassified